Conclusion and policy implications - Hazell, Peter B. R.; Ramasamy, C. (International Food Policy Research Institute, 1991)
In this study we set out to quantify the effects of the green revolution on the North Arcot region, in both the villages and the towns. For this task we had available a unique set of data obtained from household surveys undertaken in 1973/74, 1982/83, and 1983/84, which together span an era of change in the region's paddy technology.